Safety And Efficacy Of Butorphanol-Acepromazine-Glycopyrrolate As Premedicant Combination To Midazolam-Ketamine Induction And Isoflurane Maintenance In Canine Orthopaedic Surgery - Ranpariya, J.J.; Barvalia, D.R.; Padaliya, N.R.; Javia , C.B. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The objective of this study was to evaluate anaesthetic efficacy and safety of BAG (Butorphanol, Acepromazine and Glycopyrrolate) as premedicant to midazolam-ketamine induction and isoflurane maintenance in clinical canine orthopaedic cases. The clinical study was carried out in 18 cases. Dogs were premedicated with intramuscular injection of butorphanol, acepromazine and glycopyrrolate @ 0.2, 0.04 and 0.01 mg/kg b.wt. respectively, mixed in a single syringe. Induction was performed using midazolam – ketamine @ 5mg/kg b.wt. and 0.28 mg/kg b.wt., respectively administered intravenously. Anaesthesia was maintained with isoflurane. The preanaesthetic combination provided moderate to profound sedation. Induction was smooth and satisfactory in all the dogs with ketamine-midazolam and stable maintenance with isoflurane during orthopaedic procedures, viz., intramedullary pinning, limb amputation, setting Ilizarov circular external fixator and type II external fixator. BAG as preanaesthetic to ketamine-midazolam induction and isoflurane maintenance proved safe and effective in orthopaedic surgery in dogs.